Inspection of the Composite Materials - Jasim, Yaser A.; Thabet, Senan; Thabit, Thabit H. (Universitas Potensi Utama, 2018)
A non-destructive test method is the main method to examine most of the materials, composite materials in particular. There are too many Non-Destructive Test (NDT) methods to inspect the materials such as, Visual Inspection, Liquid Penetrate Inspection, Eddy-Current Inspection, Phased Array Inspection, Magnetic Particle Inspection and Ultrasonic Inspection.This paper aims to creat a unified methodology for engineers depending on reaserch onion to study the inspection of the composite materials.The researchers concluded that NDT method is the most suitable method for testing any materials and the composite materials. They also recommended to choose the most suitable NDT method as every materials and composite materials have its own properties as well as the inspection methods had its own capabilities and limitations.